2022
DOI: 10.3390/jcm11237145
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Severe Atrial Functional Tricuspid Regurgitation in Atrial Fibrillation Patients

Abstract: Background and Aim: Atrial fibrillation (AF) is an epidemic disease with a significant global health impact. Atrial functional tricuspid regurgitation (AF-TR) is a more recently acknowledged complication of AF. The main purpose of this study was to determine the prognostic value of severe AF-TR in patients with AF, and its determinants. Methods: In this retrospective, observational study, we included AF patients admitted consecutively to a tertiary clinical hospital between January 2018 and February 2020, irre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…AF-induced TR usually originates from a dilated and posteriorly displaced TV annulus, accompanied by RA enlargement and RV eccentric dilatation ( 15 , 16 ). Several studies have shown that severe AF-induced TR is a significant predictor of mortality in patients with AF ( 17 - 20 ). Although more attention has recently been drawn to isolated FTR and its prognosis, surgical treatment is uncommon, and there is still a paucity of research on the surgical outcomes of AF-induced TR ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…AF-induced TR usually originates from a dilated and posteriorly displaced TV annulus, accompanied by RA enlargement and RV eccentric dilatation ( 15 , 16 ). Several studies have shown that severe AF-induced TR is a significant predictor of mortality in patients with AF ( 17 - 20 ). Although more attention has recently been drawn to isolated FTR and its prognosis, surgical treatment is uncommon, and there is still a paucity of research on the surgical outcomes of AF-induced TR ( 21 ).…”
Section: Discussionmentioning
confidence: 99%